Using environmental DNA to elucidate range expansion of bigheaded carp in two Missouri River tributaries in eastern South Dakota - LaBrie, Lindsey A. P.; Wesner, Jeff S.; Britten, Hugh B. (North American journal of fisheries management, 2024)
Objective We used environmental DNA (eDNA) sampling methods to determine the possibility of Bighead Carp Hypophthalmichthys nobilis and Silver Carp H. molitrix (hereafter, bigheaded carp) range expansion above barriers to fish movement in two tributaries of the Missouri River in eastern South Dakota. Methods We collected water samples above and below two perceived barriers to fish movement: a natural chain of waterfalls in the Big Sioux River and a spillway at the downstream end of a man‐made reservoir in the Vermillion River. We used filtration methods to collect bigheaded carp eDNA from water samples and implemented real‐time quantitative polymerase chain reaction techniques to quantify the amount of eDNA in each sample. A total of 198 water samples and 35 field blanks were collected over 2 years (2021 and 2022). Result We detected bigheaded carp eDNA below both barriers in 2021 and 2022 and above the barrier in the Vermillion River during 2022. The median posterior prediction value for detecting eDNA below both barriers was 75.3% (95% credible interval [CrI] = 73.2–77.2%) for Bighead Carp eDNA and 54.2% (95% CrI = 51.5–56.4%) for Silver Carp eDNA. The probability of detecting eDNA above the barriers was significantly smaller: 1% (95% CrI = 0.01–1.10%) in the Big Sioux River and 1% (95% CrI = 0.01–1.30%) in the Vermillion River. Conclusion The detection of positive samples above the spillway barrier in the Vermillion River provides the first evidence that bigheaded carp may have expanded their range to habitats upstream of their documented range in eastern South Dakota. Impact statement This study demonstrates the utility of using environmental DNA sampling methods to detect bigheaded carp in areas of both known and unknown bigheaded carp presence in smaller tributary streams to the Missouri River.